2016
DOI: 10.1111/ijcp.12908
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age and erectile dysfunction diagnosis or treatment using real-world observational data in the USA

Abstract: SUMMARY Aims With self-reporting of erectile dysfunction (ED) in population-based surveys, men with ED may not represent men who are bothered sufficiently to seek an ED diagnosis and treatment. We used real-world observational data to assess: 1) the prevalence of ED diagnosis or treatment by age subgroups; and 2) the relationship of age with ED diagnosis or treatment after controlling for ED-related comorbidities in the United States. Methods This cross-sectional study used de-identified claims data (Market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 31 publications
(78 reference statements)
4
49
0
Order By: Relevance
“…Similar age distributions of ED prevalence have been reported in other studies of USA real‐world data . Our analysis also showed that, across the life span, men with ED are more likely to have comorbid CVD, DM and depression than men without ED.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar age distributions of ED prevalence have been reported in other studies of USA real‐world data . Our analysis also showed that, across the life span, men with ED are more likely to have comorbid CVD, DM and depression than men without ED.…”
Section: Discussionsupporting
confidence: 88%
“…The methodology has been described previously . Briefly, this was a cross‐sectional, non‐interventional study using claims data from the Truven Health MarketScan ® and Medicare Supplemental Research Databases .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by previous studies that have focused on treatment rates of ED compared to its reported prevalence. Observational studies in the USA indicate that significantly fewer men receive ED diagnosis and treatment than the proportion of men who experience it . Despite being a common condition, the proportion of men who seek help for ED from a doctor ranges from 22%‐26%, or 35% from a health professional in general .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ED has been estimated as nearly 40% of men >40 years of age1 although these figures are contested 2. ED increases in frequency with age and is estimated to affect 15% of men aged 40–50 years, 45% of men in their 60s and 70% of men older than 70 years 3.…”
mentioning
confidence: 99%